PENGARUH PENERAPAN BALANCE SCORECARD TERHADAP KINERJA PERUSAHAAN (Studi Empiris Pada Perusahaan Makanan dan Minuman yang Terdaftar di BEI Tahun 2019-2021) - Marsetya Nabilla Purnama; Desy Nur Pratiwi; Darmanto Darmanto (Jurnal Akuntansi dan Pajak, 2023)
This study aims to determine the effect of implementing the balanced scorecard on company performance. The population of this research is the food and beverage sub-sector manufacturing companies listed on the Indonesia stock exchange for the period 2019 – 2021. This study used purposive sampling. The samples obtained amounted to 57 samples. This study uses secondary data. Methods of data analysis using descriptive statistical tests and classic assumption tests (normality test, multicollinearity test, heteroscedasticity test, and correlation). To test the hypothesis in this study using multiple linear regression analysis, namely the F test, t test, and test the coefficient of determination (R2). The results of this study are that the financial perspective has a significant effect on company performance. The customer perspective has a significant effect on company performance. From the perspective of internal business processes, it also has a significant effect on company performance. Meanwhile, the learning and growth perspective also has a significant effect on company performance.